2020
DOI: 10.1093/heapro/daaa014
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity promotion in German vocational education: does capacity building work?

Abstract: Apprentices in many sectors are exposed to increased health risks and show low levels of physical activity (PA). Environmental and policy approaches seem to be promising tools for PA promotion as they can positively influence the context in which PA occurs. This article reports results from a German research project (2015–2018) that developed and implemented measures for PA promotion in the field of vocational education (VE). A participatory approach—cooperative planning (COP)—involving researchers as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 34 publications
2
30
0
3
Order By: Relevance
“…The PArC-AVE study, as one of these projects, combines the focus on PAHCO with a co-creation approach. Even though a qualitative study reported the implementation of cooperatively developed measures in settings of vocational education [75], it is not yet clear whether it was possible to foster aspects of PAHCO through such a complex approach. Evaluation studies are needed to prove the suitability of PAHCO for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The PArC-AVE study, as one of these projects, combines the focus on PAHCO with a co-creation approach. Even though a qualitative study reported the implementation of cooperatively developed measures in settings of vocational education [75], it is not yet clear whether it was possible to foster aspects of PAHCO through such a complex approach. Evaluation studies are needed to prove the suitability of PAHCO for interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Given this preference, it can be assumed that this sample tends to target those individuals who are less interested in or familiar with the topics of PA and health. Within the scope of the PArC-AVE Study (Popp et al, 2020), as a part of the research consortium Capital4Health (here project phase 2), we asked all representatives of the Working Group Sport Science and Sport of the Universities in Bavaria (AKS), who coordinate the basic qualification programs in physical education at their universities (n = 8), to support the statewide survey in the winter term 2018/2019. All those coordinators were willing to organize the distribution and collection of paper-pencil questionnaires or, if desired, to provide the students with access to an equivalent online survey.…”
Section: Teaching Students (Study 2)mentioning
confidence: 99%
“…In Bavaria, Germany, the basic qualification program is a compulsory compact certificate for all ongoing elementary, middle, and special education teachers who choose physical education neither as a primary subject (German: Hauptfach) nor as a minor subject (German: Didaktikfach). Within the scope of the PArC-AVE Study (Popp et al, 2020), as a part of the research consortium Capital4Health (here project phase 2), we asked all representatives of the Working Group Sport Science and Sport of the Universities in Bavaria (AKS), who coordinate the basic qualification programs in physical education at their universities (n = 8), to support the statewide survey in the winter term 2018/2019. All members were willing to organize the distribution and collection of paper-pencil questionnaires or, if desired, to provide the students with access to an equivalent online survey.…”
Section: Teaching Students (Study 2)mentioning
confidence: 99%